Population structure of the giant tiger shrimp Penaeus monodon in Bangladesh based on variation in microsatellites and immune-related genes. Issue 7 (8th August 2016) - Alam, M. M. Mahbub; Pálsson, Snæbjörn
ABSTRACT: Penaeus monodon is the most economically important penaeid shrimp in the Indo-West Pacific region for both aquaculture and wild capture. This study evaluated the population structure of P. monodon in Bangladesh and searched for signs of natural selection in immunological genes. Wild P. monodon sampled at four locations off Bangladesh were studied using 10 microsatellite markers and 14 single nucleotide polymorphic sites (SNPs), including six unannotated regions and eight immunological genes (seven C-type lectin and one HLA3 ), of which variations were associated with tolerance to pathogens and survival in aquaculture. Three genetically distinguishable populations were observed, one in the eastern mangrove forest in the Sundarban–Barguna coast (south Bangladesh), the second in the Sundarban–Middle ground close to the delta of the river Ganges and the third at St Martin's Island, southeastern Bangladesh. ranged from 0.042 to 0.093, and significant FST ranged from 0.004 to 0.011. A large proportion of individuals caught in Middle ground and at St Martin's Island showed a genetic origin that was distinct from the other individuals at those sites, possibly from unsampled southern regions in the Bay of Bengal. Variation and the FST values for the SNPs from C-type lectin genes and HLA3 did not differ from the other markers studied, indicating no selective effects at these loci in the natural populations. Sustainable management of P. monodon should consider the population differentiation described in this study. Further assessment of signs of selection in aquaculture stocks could be useful for successful breeding of the species.